Ethylene-mediated enhancement of apical hook formation in etiolated Arabidopsis thaliana seedlings is gibberellin dependent. - Vriezen, W; Achard, P; Harberd, N; Van Der Straeten, D (2004)
Dark-grown Arabidopsis seedlings develop an apical hook by differential elongation and division of hypocotyl cells. This allows the curved hypocotyl to gently drag the apex, which is protected by the cotyledons, upwards through the soil. Several plant hormones are known to be involved in hook development, including ethylene, which causes exaggeration of the hook. We show that gibberellins (GAs) are also involved in this process. Inhibition of GA biosynthesis with paclobutrazol (PAC) prevented hook formation in wild-type (WT) seedlings and in constitutive ethylene response (ctr)1-1, a mutant that exhibits a constitutive ethylene response. In addition, a GA-deficient mutant (ga1-3) did not form an apical hook in the presence of the ethylene precursor 1-aminocyclopropane-1-carboxylate (ACC). Analysis of transgenic Arabidopsis seedlings expressing a green fluorescent protein (GFP)-repressor of ga1-3 (RGA) fusion protein suggested that ACC inhibits cell elongation in the apical hook by inhibition of GA signaling. A decreased feedback of GA possibly causes an induction of GA biosynthesis based upon the expression of genes encoding copalyl diphosphate synthase (CPS; GA1) and GA 2-oxidase (AtGA2ox1). Furthermore, expression of GASA1, a GA-response gene, suggests that differential cell elongation in the apical hook might be a result of differential GA-sensitivity.